The future of haematology: inspiring others to join us on our noble journeys. (15th November 2020) - Butler, Tom
Summary: The Chair of Education Committe of the British Society for Haematology (BSH) introduces the winning entry for the BSH 2020 Student Essay competition. This is part of the BSH 60th anniversary celebrations.